Development of Interactive Learning Media Assisted by Google Sites in Building Materials for Elementary Schools Grade V - Ria Astarina; Yerizon; Alwen Bentri; Melva Zainil (Postgraduate, University of Mataram, 2024)
This research is motivated by the lack of use of multimedia in Mathematics learning in elementary schools, teachers more often use one-way based learning media which will make students feel bored. The aim of this research is to develop interactive learning media assisted by Google Sites on Class V Elementary School Building Materials. This research uses research and development (R&D) methods using the 4D development model (Define, Design, Develop, Disseminate). Data collection in this research uses a questionnaire to determine expert assessments of media and test media practicality. Effectiveness testing is carried out using tests. In the Define stage, an initial analysis of the curriculum and students is carried out. In the Design stage, the design of the Flowchart and Storyboard for the Google Sites interactive media being developed is carried out. Validation by experts on Google Sites media in the material aspect received a score of 91.56% in the Very Valid category, in the media aspect it received a score of 61.33% in the Valid category, and in the language aspect it received a score of 84.23% in the Very Valid category. Furthermore, the results of the practicality test by the teacher got a score of 97.33% and the students got a score of 88.33% in the Very Practical category. The results of the effectiveness test showed that the average student score was 90.92, there was an increase in the students' knowledge score. Meanwhile, the average N-Gen Score obtained from the difference between students' pre-test and post-test scores obtained a percentage value of 79.31% in the Effective category. From the research carried out, it can be concluded that Interactive Learning Media Assisted by Google Sites in Building Materials for Class V Elementary Schools is valid, practical and effective interactive media, so it can be used in the learning process.